علم العروض ومشكلات تعلّمه لدى الطلبة: قضايا وحلول = Problems of learning Arabic prosody among students: issues and solutions - Ahmad Safian, Nursafira; Ahmad Radzi, Najwa Hanani (Department of Arabic and Middle Eastern Languages, Faculty of Languages and Linguistics, University of Malaya, 2019)
يتطرق هذا البحث إلى استيعاب المشاكل التي يواجهها الطلبة العرب في غضون دراسة علم العروض. ويهدف البحث إلى كشف الصعوبات التي يعاني منها هؤلاء الطلبة حتى تؤثر على مستوياتهم فيحصلون على نواتج الاختبار المتدنية، ومن ثم تقديم الحلول المقترحة لتذلل هذه الصعوبات. ويستخدم هذا البحث الاستعراض المنهجي للدراسات السابقة (Systematic Literature Review)؛ حيث إنه يعرض في بداية الدراسة مقدمات عامة عن علم العروض ومفهومه، والبحور الشعرية، قبل أن يتناول مشكلات تعلّم علم العروض لدى الطلبة العرب، وطرق حل هذه المشكلات. وقد خلص البحث إلى أن المشكلات التي يواجهها الطلبة في دراسة علم العروض تمس جوانب ثلاثة؛ أولها: منهج التعليم وأسلوب المعلمين، وثانيها: الكتاب المقرر والمادة الدراسية، وثالثها: نفور الطلاب والدارسين من المادة. أما بالنسبة لطرق معالجة هذه المشاكل فمن أهمها: خلق المحيط التفاعلي بين الدارسين والمدرسين في قاعات الفصل، مثل: توظيف الوسائل التكنولوجية الحديثة، وتقديم المادة الدراسية في إطار نغمي موسيقي، وطرح المادة بدءا بها من السهل إلى الصعب، حتى أصبحت دراسة العروض مادة حية تطبيقية، يمكن استشعار حلاوتها لدى الطلاب. ************************************************************************************** This study discusses the problems faced by Arab students in learning Arabic prosody. This study aims to expose the difficulties experienced by the students, which affected their achievement; therefore, they did not score good results in examination. Besides, this study exposes the solutions to overcome those difficulties. The design of this study is a systematic literature review, in which the researchers explained generally about Arabic prosody, its concept and poetic meters at the beginning of the study, before discussing the problems faced by the students as well as the solutions. This study conclude that the problems faced by the students in learning Arabic prosody are related to three main aspects; namely method of teaching practiced by the instructors, the syllabus and books being used and the aversion of students toward Arabic prosody. Among the most important solutions to overcome difficulties in learning Arabic prosody are creating an interactive environment between two parties: students and instructors in the classrooms. These include the usage of modern technological tools, teaching Arabic prosody using musical tunes and learning subject matter according to the range of difficulty levels. By using these methods, the researchers believed that the students paid more attention in learning Arabic prosody; hence, they could understand the course in an effective way.